Inventory of Potentially Allelopathic Plants in Laut Dendang Village and Their Effects on Mustard Greens (Bransica juncea l.) - indayana Febriani Tanjung; Ayu Sahara Tumanggor; M Rizki; Nada Thahira; Febry Ramadhani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Allelopathy comes from the Greek words allelon, which means